(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In preschool children with lagging psychical development of future logopeds, a non-gross speech defect is manifested in such difficulties as impaired sound pronunciation, dictionary cambagality and insufficient differentiation, mastering lexical-grammatical constructions. In most children, phonetic-phonematic perception is insufficient, hearing-speech memory decreases, the implementation of the process of development of speech is aimed at regulating its interrelated elements, following logopedic games in logopedic training, targeting, focusing more on logopedic games in the process of logopedic training